SEMIOTIC ANALYSIS OF ANIMATED TV SERIES `RIKO: JARAK MATAHARI_BUMI '' AS AN EDUCATIONAL MEDIA FOR CHILDREN - Lani Aisyah (Politeknik Negeri Media Kreatif, 2020)
Children are an age group who adapts very well to the stimuli what they receive from their environment, such as movies and games. Unfortunately, entertainment these days contains many negative messages that has an impact on the erosion of moral values, which are, then implemented in the form of negative thought patterns and behaviors.The purpose of this research is to examine how children's entertainment media can be educational, entertaining, and easy to understand with a case study of the animated tv series ‘Riko: Jarak Matahari dan Bumi’This research was studied using the method of pragmatic semiotics initiated by Charles Sanders Peirce by analyzing semiotic elements, then validated with the psychological theory of child development. The results of the analysis show that the semiotic elements presented in ‘‘Riko: Jarak Matahari dan Bumi’ are in line with the psychological principles of child development.